2013
DOI: 10.1074/jbc.m113.466946
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Prothrombin Reveals Conformational Flexibility and Mechanism of Activation

Abstract: Background: The x-ray structure and mechanism of activation of prothrombin remain elusive. Results: X-ray and solution studies document conformation flexibility of prothrombin. The two sites of cleavage at Arg-271 and Arg-320 have distinct solvent accessibility. Conclusion: Burial of Arg-320 prevents prothrombin autoactivation and directs prothrombinase to cleave at Arg-271 first. Significance: A structure-based mechanism of prothrombin activation emerges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 47 publications
3
54
0
2
Order By: Relevance
“…In the absence of histone H4, the slowest lifetime of 603 s refers to the decay of the donor-only control, the short lifetime of 28 Ϯ 3 s with 45% population has a distance between Ser-101 in kringle-1 and Ser-210 in kringle-2 of Յ34 Å, and the long lifetime of 272 Ϯ 8 s with 55% population has a distance of 54 Ϯ 2 Å. These results are practically identical to those reported recently (5). Under saturating concentrations of histone H4 the lifetime of the collapsed conformation remains unchanged, but a new lifetime of 170 Ϯ 5 s corresponding to a distance between the probes of 47 Ϯ 2 Å replaces the one pertaining to the fully extended conformation.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…In the absence of histone H4, the slowest lifetime of 603 s refers to the decay of the donor-only control, the short lifetime of 28 Ϯ 3 s with 45% population has a distance between Ser-101 in kringle-1 and Ser-210 in kringle-2 of Յ34 Å, and the long lifetime of 272 Ϯ 8 s with 55% population has a distance of 54 Ϯ 2 Å. These results are practically identical to those reported recently (5). Under saturating concentrations of histone H4 the lifetime of the collapsed conformation remains unchanged, but a new lifetime of 170 Ϯ 5 s corresponding to a distance between the probes of 47 Ϯ 2 Å replaces the one pertaining to the fully extended conformation.…”
Section: Resultssupporting
confidence: 81%
“…The recent crystal structure of prothrombin along with LRET measurements have revealed that kringle-1 moves similar to a dumbbell relative to the rest of the zymogen due to the extreme flexibility of the linker connecting the two kringles (5). As a result, prothrombin assumes two alternative conformations in solution: a fully extended conformation with a population of 55% where Ser-101 in kringle-1 and Ser-210 in kringle-2 are separated by a distance of 54 Ϯ 2 Å, and a collapsed conformation with a population of 45% where Ser-101 in kringle-1 and Ser-210 in kringle-2 are separated by a distance of Յ34 Å or are at least 20 Å closer than in the fully extended conformation (5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations